STUDI PEMANFAATAN TUMBUHAN OBAT SEBAGAI TONIK OLEH PENGOBAT TRADISIONAL DI DESA KARYA BAKTI KECAMATAN SUNGAI BETUNG KABUPATEN BENGKAYANG - Riconadi, Riconadi; Arbiastutie, Yanieta; Mariani, Yeni; Sisillia, Lolyta; Yusro, Fathul (JURNAL HUTAN LESTARI, 2020)
There is a long history of the plant's usage as medicine to overcome various diseases and maintain people's health conditions in communities.Â  Among its multiple benefits, medicinal plants are also used to strengthen the body organs (tonic). The use of medicinal plants as tonics is still carried out by the society of Karya Bakti Village, Sungai Betung District, Bengkayang Regency, especially by traditional healers (dukun) who are trusted by the community to help treat various diseases. This study aims to analyze plant's use by traditional healers in Karya Bakti Village, Bengkayang Regency. The data was collected by interviewing two traditional healers who were selected based on the snowball sampling technique. The interview results revealed that the village's traditional healer used 32 species of medicinal plants belonging to 25 families. The most widely used plant family is Zingiberaceae (19%), with the highest habitus is herbs (31.25%). The most commonly used part is the root (28.13%), the form of single ingredients (53%) by boiling processing (74.36%), the administration is orally (77.5%) with a frequency of use three times a day (75%). The study results proved that traditional healers in Karya Bakti Village were still using medicinal plants as tonics.Keywords: medicinal plants, tonic, traditional healersÂ